Pengembangan Minat Baca Dan Literasi Anak-Anak Desa Bandar Magodang Melalui Kegiatan Pengabdian Masyarakat Mahasiswa UIN Sumatera Utara - Ajeng Sri Hadimiati; Riska Dewi; Siti Nurmala; Siti Salamah Br Ginting (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Community Service activities are mandatory activities carried out by UIN North Sumatra students, especially at the Faculty of Tarbiyah and Teacher Training. PMM-4 students carry out Community Service activities in Bandar Magodang Village, Bintang Bayu District. One of the series of activities planned by PMM-4 students is the Learning House which is attended by the children of Bandar Magodang Village. The existence of this learning house program aims to help the children of Bandar Magodang village in increasing their interest in reading and writing skills in the midst of the widespread use of gadgets. This program runs well, this service activity is carried out through 3 stages, namely planning, implementation, and evaluation. The method used in the implementation of community service is a qualitative approach. The research subjects of this study were Bandar Magodang village children who were actively learning when a learning house was held by PMM-4 students children are asked to read books and their questions are also asked to write questions and answer questions in their notebooks. This learning house activity will be carried out on August 18-19, 2023 at 14.00 – 16.00 WIB in one of the yards of Bandar Bagodang Village residents, Bintang Bayu District.